2022
DOI: 10.1007/s10680-022-09610-x
|View full text |Cite
|
Sign up to set email alerts
|

An Age-Period-Cohort Approach to Analyse Late-Life Depression Prevalence in Six European Countries, 2004–2016

Abstract: Late-life depression is a condition that affects an ever-growing share of the population in ageing societies. While depression prevalence varies across countries for a myriad of reasons, generational factors, expressed in the shared experience of birth cohorts, may also play a part in such differentials. This paper describes the presence of age, period, and cohort (APC) effects in late-life depression prevalence trends (for adults aged 50 and above) for selected countries in Europe, using the Survey of Health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 45 publications
2
5
1
Order By: Relevance
“…Although women have a longer life expectancy, the prevalence of depression is also higher among them (Salk et al, 2017 ). Consistently, previous research has shown a differential impact of depression on healthy life expectancies, depending on gender, with women at all ages expecting to live a higher proportion of their life with depression (Andrade et al, 2016 ; Alves and Pereira, 2018 ; García et al, 2019 ; Wu et al, 2021 ; Bramajo, 2022 ).…”
Section: Introductionsupporting
confidence: 71%
“…Although women have a longer life expectancy, the prevalence of depression is also higher among them (Salk et al, 2017 ). Consistently, previous research has shown a differential impact of depression on healthy life expectancies, depending on gender, with women at all ages expecting to live a higher proportion of their life with depression (Andrade et al, 2016 ; Alves and Pereira, 2018 ; García et al, 2019 ; Wu et al, 2021 ; Bramajo, 2022 ).…”
Section: Introductionsupporting
confidence: 71%
“…Previous studies in US and European samples had provided conflicting evidence regarding the existence of a cohort effect in trends in depressive symptoms, with some providing support for a cohort effect (Bramajo, 2022 ; Sullivan et al, 2020 ; Twenge et al, 2019 ), and others providing no support for it (Keyes et al, 2019 ; Spiers et al, 2011 ). As I found evidence for a general cohort effect in Germany, the current study supports the existence of a cohort effect in depression trends.…”
Section: Discussionmentioning
confidence: 99%
“…Using an English sample, they found little evidence for changes in common mental disorder over time. Contrasting with these results, Bramajo ( 2022 ) recently analyzed trends in depression in six European countries, including Germany. Using age-period-cohort methods, they found increases in the prevalence of depression among younger born cohorts, especially among men.…”
Section: Introductionmentioning
confidence: 99%
“…The decision to merge two consecutive waves when possible was led by the otherwise relatively small sample size of some ethnic groups that would have been unsuitable for an APC analysis. This strategy has been used in the past, see Bramajo (2022) . This process was followed for all waves except for 2018, which was not combined with 2020.…”
Section: Methodsmentioning
confidence: 99%